Humanity : A Moral History of the Twentieth Century - Glover, Jonathan (New Haven, CT Yale University Press, 2001)
The twentieth century was the most brutal in human history, featuring a litany of shameful events that includes the Holocaust, Hiroshima, the Stalinist era, Cambodia, Yugoslavia, and Rwanda. This important book looks at the politics of our times and the roots of human nature to discover why so many atrocities were perpetuated and how we can create a social environment to prevent their recurrence.
Include Reference, Source and Index
Originally Published: London : J. Cape. 1999
Keywords: Political ethics -- Humanity -- War